The role of mangrove in the French Guiana shrimp fishery. Issue 2 (3rd April 2019) - Diop, Bassirou; Sanz, Nicolas; Blanchard, Fabian; Walcker, Romain; Gardel, Antoine
ABSTRACT: This paper investigates the role of mangrove as an habitat in the evolution of the French Guiana shrimp stock to explain the recent collapse of shrimp production. To achieve our aim, we use the open access fishery model developed by Barbier and Strand [1998. "Valuing Mangrove-Fishery Linkages-A Case Study of Campeche, Mexico." Environmental and Resource Economics 12: 151–166] and integrate mangrove surface into the shrimp natural growth function. This enables to account directly for the effects of mangrove surface changes on the stock dynamics and thus production. Our results indicate that financial losses in the French Guiana shrimp fishery increase when mangrove surface decreases and are mitigated when mangrove surface increases. We show that changes in mangrove surface are not determinant in explaining the collapse of the shrimp stock but that mangrove should be preserved as it still mitigates the decline of the stock.